Memorial Art Gallery of the University of Rochester - Anonymus, A. (1961)
Rochester, N. Y., Memorial Art Gallery of the University of Rochester; Handbook; 6: 3 in. terracotta figure bearing offering, OB Larsa; 7: relief, kneeling figure of a winged genius, Nimrud (palace of Aššurnasirpal II).